Identifying and validating the dimensions and components of improving the medical education system in the implementation of online curricula - Zandieh , Gita; Etemad Ahri, Aladdin; Rashidi , Zolfaghar (Social Determinants of Health, 2024)
Background: The current research was conducted with the aim of identifying and validating the dimensions and components of online curriculum implementation. Methods: The research was conducted with a mixed approach. In order to collect information in the qualitative part after studying the sources, 25 faculty members in the fields of educational management and curriculum planning of medical science groups were purposefully selected and semi-structured interviews were conducted. In the quantitative part, based on the results of qualitative part, an online curriculum implementation questionnaire was compiled with the aim of determining the components of the improvement of the medical education system. The validity of the questionnaire was obtained from factor analysis and reliability from the index of Cronbach's alpha coefficient and composite reliability. The questionnaire was distributed among 380 professors of different disciplines. The results were analyzed using the univariate t test. Results: The results of the qualitative part showed that the implementation of the online curriculum included 11 dimensions, 36 components and 123 concepts. The results of the quantitative part also showed the validity of the identified dimensions and components, and the validity and reliability of the variables were confirmed. The results of the univariate t-test showed that the status of online curriculum implementation dimensions was moderate to high. Conclusion: The online implementation of the curriculum requires the combination of synchronous and asynchronous education for better participation and access of students to the subjects at any time without restrictions and establishing communication and interaction between students and professors.